The Functional Defect of Factor VIII Leiden, a Genetic Variant of Coagulation Factor VIII - Mertens, K; van Wijngaarden, A; Bertina, R M; Veltkamp, J J (Thrombosis and Haemostasis, 1985)
Factor VIII Leiden is a genetic variant of coagulation factor VIII which has been detected in the plasma of a patient with mild haemophilia A. In this patient’s plasma factor VIII procoagulant antigen was in 5-fold excess over factor VIII procoagulant activity, indicating the presence of an abnormal factor VIII molecule. The variant factor VIII was isolated from the patient’s plasma, and its functional properties were studied in a factor X-activating system consisting of purified components. The isolated factor VIII Leiden was normally activated by factor Xa and by thrombin, but the activity of the factor Villa was about 3% of normal. The defect of factor Villa Leiden was studied by comparison with normal factor Villa in kinetic experiments of factor Xa formation. The results support the hypothesis that factor Villa Leiden has a reduced affinity for phospholipid-bound factor IXa in the intrinsic factor X-activating complex.
Keywords: Factor VIII; Genetic variant; Haemophilia A+; Factor X activation